Safety of Spironolactone in Dogs with Chronic Heart Failure because of Degenerative Valvular Disease: A Population‐Based, Longitudinal Study. (19th July 2013) - Lefebvre, H.P.; Ollivier, E.; Atkins, C.E.; Combes, B.; Concordet, D.; Kaltsatos, V.; Baduel, L.
<x xml:space="preserve">Abstract</x> Background Spironolactone treatment in humans is associated with an increased risk of hyperkalemia and renal dysfunction. Hypothesis Dogs with cardiac disease treated with spironolactone, in addition to conventional therapy, are not at higher risk for adverse events (AEs) than those receiving solely conventional therapy. Animals One hundred and ninety‐six client‐owned dogs with naturally occurring myxomatous mitral valve disease. Methods Prospective, double‐blinded field study with dogs randomized to receive either spironolactone (2 mg/kg once a day) or placebo in addition to conventional therapy (angiotensin‐converting enzyme inhibitor, plus furosemide and digoxin if needed). Safety was compared between treatment groups, using the frequency of AEs, death caused by cardiac disease, renal disease, or both, and variations in serum sodium, potassium, urea, and creatinine concentrations. For the latter, population‐specific reference intervals were established and out of range values (ORV) analyzed. Results The number of AEs was similar in the spironolactone and reference groups (188 and 208, respectively), when followed for median duration of 217 days (range [2–1, 333]). At each study time point, the percentage of dogs showing ORV was similar between groups. There were a higher number of deaths because of cardiac disease, renal disease or both in the reference group (30.7% versus 13.7%) (P = .0043). Conclusions and Clinical Importance Dogs with heart failure receiving spironolactone in addition to conventional treatment are not at a higher risk for AEs, death caused by cardiac disease, renal disease, or both, hyperkalemia, or azotemia.